Color preferences among selected adults in Ghana - Adjah, John; Bekoe, Stephen; Decardi-Nelson, Agnes; Afeafa Ry-Kottoh, Lucy; Kalognia, Joshua (Journal of Graphic Engineering and Design, 2024)
This paper presents a study on color preferences among a sample of Ghanaian adults. Two surveys were conducted, with a total of 143 participants (50 in Survey 1, and 93 in Survey 2). The participants completed both printed and digital questionnaires to gather data on their color preferences. The results showed that blue was the most preferred color by both males and females in general, but not for specific items. In survey 2, a chi-square test on categorical variables revealed a significant relationship between gender and preference for light, dark, or bright colors (p=0.025), as well as gender and number of preferred colors per personal item (p=0.02). However, no significant relationships were found between gender and change of colors from childhood (p=0.73), gender and number of preferred colors (p=0.204), gender and most preferred colors (p=0.216), age, and the number of preferred colors (p=0.19). Interestingly, 66.3% of the participants in Survey 2 indicated that their preferred colors were based on innate attraction, regardless of whether their color preferences had changed or remained the same since childhood. Overall, blue and red were the most preferred colors, with a score of 34.4%. These findings provide valuable insights for design practitioners and communicators and offer a basis for future research on color preferences among Ghanaians.